The space ship under the apple tree - Slobodkin, Louis 1903- (New York Macmillan, 1952)
When a junior scientist explorer from the planet of Martinea crashlands on Eddie's grandmother's farm, Eddie spends his summer searching for a way for Marty to get back home again.
Keywords: Extraterrestrial beings -- Fiction; Science fiction